Blake Edwards interviews - Edwards, Blake 1922-2010 (University Press of Mississippi, 2018)
Blake Edwards (1922-2010) was a multitalented, versatile director constantly exploring who he was, not only in filmmaking but also in life. Often typecast as a comedy director, he also created westerns, thrillers, musicals, and heart-wrenching dramas. His strength as a filmmaker came from his ability to be a triple threat--writer, director, and producer--allowing him full control of his films, especially when the studio system failed him. Blake Edwards: Interviews highlights how the filmmaker created the hugely successful Pink Panther franchise; his long partnership with award-winning composer Henry Mancini; his principles of comedy as influenced by the comic greats of film history, especially silent comedies; his decades-long marriage and film collaborations with Julie Andrews; and his unique philosophy of life. Continually testing his abilities as a writer, which he considered himself to be above all other professions, Edwards did not hesitate to strip comedy from films that clearly and purposefully explored other genres with sharp, dramatic insight. He created thrilling suspense (Experiment in Terror); rugged westerns (Wild Rovers); riveting drama (Days of Wine and Roses); and bittersweet romance (Breakfast at Tiffany's). He also created musicals, Namely Darling Lili and Victor/Victoria, showcasing the talents of Andrews. In fact, many of these films have been considered some of Edwards's finest in his appreciable career.0Reinventing himself throughout his sixty-year career, Edwards found new outlets of expression that fueled his creativity to the very end. This long-overdue collection of published interviews explores the ups and downs--and ups again--of a sometimes flawed but always gifted and often surprising filmmaker
Keywords: Edwards, Blake -- 1922-2010; Regisseur; Filmproduzent; Drehbuchautor; Edwards, Blake / 1922-2010 / Interviews; Motion picture producers and directors / United States / Interviews; Producteurs et réalisateurs de cinéma / États-Unis / Entretiens; PERFORMING ARTS / Individual Director (see also BIOGRAPHY & AUTOBIOGRAPHY / Entertainment & Performing Arts); PERFORMING ARTS / Film & Video / Direction & Production; BIOGRAPHY & AUTOBIOGRAPHY / Entertainment & Performing Arts; Edwards, Blake / 1922-2010; Motion picture producers and directors; United States; Interview